The challenges of prosecuting crimes of sexual violence in armed conflict under international criminal law - Šūtava, Paula (Riga Graduate School of Law, 2023)
This research explores the challenges of prosecuting crimes of sexual violence during armed conflict under international criminal law. Despite the prevalence of sexual violence in armed conflicts, prosecution rates remain low. The aim of the study is to identify the main challenges in prosecuting such crimes. The research question of the topic is - What are the challenges of prosecuting crimes of sexual violence in armed conflict under international criminal law? Through doctrinal research, the author concludes that the main challenges include inadequate law enforcement competence, lack of resources caused by the armed conflict, and possibility of forum shopping. Procedural matters, such as lack of jurisdiction, are often significant obstacles, as well as the collection of evidence and sensitive nature of such crimes. Overall, this research highlights the need for improved support system for victims of sexual violence during armed conflicts and greater international cooperation to address the challenges of prosecuting sexual violence during armed conflicts.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; International criminal law; International Criminal Court; sexual violence; armed conflicts